Annealing‐Free Thioantimonate Argyrodites with High Li‐Ion Conductivity and Low Elastic Modulus (Adv. Funct. Mater. 11/2023). (10th March 2023) - Jung, Wo Dum; Kim, Ji‐Su; Kim, Young Jung; Jeong, Hyeseong; Han, Daseul; Nam, Kyung‐Wan; Ahn, Docheon; Kwon, Deok‐Hwang; Jung, Hun‐Gi; Lee, Jong‐Ho; Kim, Hyoungchul
Abstract : Annealing‐Free Process In article number 2211185, Hyoungchul Kim and co‐workers develop a solid electrolyte (SE) with high Li‐ion conductivity and low elastic modulus by annealing‐free milling and present it as a chess game. Three chess pieces (pawn, queen, and rook) are here depicted as three advantages of the new SE (ductility, annealing‐free milling, and superconductivity). With all these advantages, the new batteries (White King) overwhelm the conventional ones (Black King).